Möglichkeiten und Grenzen eines Malzbiers auf einem stagnierenden Markt: Das Beispiel Vitamalz; Opportunities and Limitations of a Malt Beer in a Stagnating Market: The Example of Vitamalz - Nancy Bodden (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte (VSWG), 2024)
– In the 1970s, the German malt beer market was a niche market that had not developed in parallel with the general increase in beer consumption and the strong growth in soft drinks consumption in the post-war years. Malt beer also had the image of being a drink for children and nursing mothers. In this difficult market, the output of the malt beer brand Vitamalz more than doubled over the course of the 1970s. The article illustrates the success strategies: The conception of an attractive branded malt beer based on modern marketing methods as well as the production and national distribution in a license network of several medium-sized breweries. But the growth was only achieved at the expense of other malt beer brands, while previous non-malt beer drinkers were hardly reached.
Keywords: N34; N64; N84; 330; malt beer; marketing; market research; license system; Vitamalz; Karamalz